2015
DOI: 10.1590/0103-64402013x0024
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Restoration Thickness and Time after Light-Activation Effects on Degree of Conversion of Resin Cement

Abstract: This study evaluated the effects of indirect restorative materials, curing conditions and time on the degree of conversion (DC) of a dual-cured resin cement using infrared spectroscopy. The resin cement (RelyX Unicem 2, 3M ESPE) was applied to the diamond surface of a horizontal attenuated-total-reflectance unit and activated using one of following conditions: self-cure, direct light exposure, light exposure through indirect restorative materials (resin nano-ceramic: Lava Ultimate, 3M ESPE or feldspathic ceram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
1
9
0
6
Order By: Relevance
“…These data are consistent with other studies in the literature. 9,12,19,20 In the present study, the light activation protocols, as well as the different opacities of the interposed ceramics significantly influenced the color change after 8 days of storing in dry dark canisters (post-irradiation conversion). The delayed light activation caused higher color change than the immediate activation (Figs 1 and 2).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…These data are consistent with other studies in the literature. 9,12,19,20 In the present study, the light activation protocols, as well as the different opacities of the interposed ceramics significantly influenced the color change after 8 days of storing in dry dark canisters (post-irradiation conversion). The delayed light activation caused higher color change than the immediate activation (Figs 1 and 2).…”
Section: Discussionmentioning
confidence: 65%
“…This continued polymerization consists in the conversion of monomers even after the light activation process and can happen for days after the cementation. These data are consistent with other studies in the literature …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The indirect materials commonly used are composite resins, glass and polycrystalline (or zirconia) ceramics, which present different optical and light absorption properties that influence light attenuation during light-activation of an underlying resin cement. [77][78][79][80] To overcome the effects of curing light attenuation, dual-cured cementing systems were developed and some of them are used in combination with adhesive systems, which contain co-initiators, such as sulfinic acid salts that produce free radicals and contribute to the polymerization reaction of the dual-cured resin cements. [81][82] However, when light activated the most of cementing systems generate higher degree of conversion values than autopolymerizing mode, which can compromise some properties of resin cement, such as flexural strength, modulus, hardness, solubility and water sorption.…”
Section: Light Attenuation By Absorbing Characteristics Of Indirect Rmentioning
confidence: 99%
“…This study did not find significant differences between materials when using the same thickness and reported that the light attenuation caused by 2.0-mm thick millable materials for CAD-CAM system resulted in significantly lower degree of conversion than those obtained with thin materials (0.5 and 1.0 mm thick), which did not differ from the direct light exposure of resin cement (without material interposition). 80 Effects of curing light on the temperature of tooth pulp and soft tissues…”
Section: Light Attenuation By Absorbing Characteristics Of Indirect Rmentioning
confidence: 99%